FACTORES DE RIESGO BIOMECÁNICO EN LA PERCEPCIÓN DE LA CALIDAD DE VIDA LABORAL DE LOS TRABAJADORES DE UNA EMPRESA DE SERVICIOS GENERALES - Kelly Palomino Osorio; Luisa Forero Perea; Lizeth Álvarez Fernández; Gina Fuentes Rojas (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2023)
The quality of working life with respect to work environments is increasingly demanding. Therefore, the need arises tostudy the conditions for the execution of their daily tasks. The objective of this research is to establish the biomechanicalrisk factors in the perception of quality of life of the employees of the general services area of a cleaning and maintenancecompany.The company under study is a cleaning and maintenance company based in Bogotá, which has more than 15years of experience, a sample of 60 women aged 25 to 57 years was chosen. This is a non-experimental cross-sectionalinvestigation with a mixed approach. It was evidenced that the interpretation of the risk in all cases is not acceptable andthat they require specific control, a high level of satisfaction of the workers is observed regardless of the presence ofailments. People who work in general services present musculoskeletal disorders, due to the multiple discomforts thatthey may present during the activities they carry out, hence the importance of implementing prevention strategies.